2021
DOI: 10.1093/nar/gkaa1204
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin regulatory dynamics of early human small intestinal development using a directed differentiation model

Abstract: The establishment of the small intestinal (SI) lineage during human embryogenesis ensures functional integrity of the intestine after birth. The chromatin dynamics that drive SI lineage formation and regional patterning in humans are essentially unknown. To fill this knowledge void, we apply a cutting-edge genomic technology to a state-of-the-art human model of early SI development. Specifically, we leverage chromatin run-on sequencing (ChRO-seq) to define the landscape of active promoters, enhancers and gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Fetal-specific subsets included proximal progenitors (FGG, BEX5) as described in refs. [1][2][3]52 , distal progenitors enriched for colon genes (CKB, AKAP7, GPC3) and CLDN10 cells that are possibly pancreatic progenitors based on expression of DLK1, PDX1, RBPJ, CPA1 and SOX9 53 . This population also highly expressed CLU, a marker for intestinal revival stem cells that has previously been described 54 .…”
Section: Cell-type Annotationmentioning
confidence: 99%
“…Fetal-specific subsets included proximal progenitors (FGG, BEX5) as described in refs. [1][2][3]52 , distal progenitors enriched for colon genes (CKB, AKAP7, GPC3) and CLDN10 cells that are possibly pancreatic progenitors based on expression of DLK1, PDX1, RBPJ, CPA1 and SOX9 53 . This population also highly expressed CLU, a marker for intestinal revival stem cells that has previously been described 54 .…”
Section: Cell-type Annotationmentioning
confidence: 99%
“…Indeed, we observed high transcriptional activity around the miR-375 locus only in the DE stage, but not in other stages including Duo spheroids ( Figure 6B ). We mined previously defined transcriptional regulatory elements (TREs) in the hPSC-HIO model (26) and found that four out of the six TREs adjacent to the miR-375 locus (TRE#2, #3, #4 and #6) are uniquely active in DE ( Figure 6B ). We also observed that the summed transcriptional activity of putative enhancer TREs (TRE#1-4) is highly correlated with the transcriptional activity of TREs overlapping with the putative promoter region of miR-375 (TRE#5-6) across all four stages of the directed differentiation model ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin run-on sequencing: Chromatin isolation for chromatin run-on sequencing (ChRO-seq) was performed as previously described (25,26). To perform run-on reaction with the isolated chromatin, samples were mixed with an equal volume of 2X run-on reaction mix [10 mM Tris-HCl pH 8.0, 5 mM MgCl2, 1 mM DTT, 300 mM KCl, 400 μM ATP, 0.8 μM CTP, 400 μM GTP, 400 μM UTP, 40 μM Biotin-11-CTP (Perkin Elmer, Waltham, MA; NEL542001EA), 100 ng yeast tRNA (VWR, 80054-306), 0.8 units/μL SUPERase In RNase Inhibitor, 1% (w/v) Sarkosyl].…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
See 2 more Smart Citations